2021
DOI: 10.1007/s15010-021-01643-4
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant Acinetobacter baumannii infections in COVID-19 patients hospitalized in intensive care unit

Abstract: Objectives Superinfections in patients hospitalized in intensive care unit (ICU) are an important and challenging complication, also in COVID-19. However, no definitive data are available about the role of multidrug-resistant Acinetobacter baumannii (MDR-AB) in COVID-19. Methods This was a single-center, cross-sectional study including patients with MDR-AB infections admitted to ICU with or without COVID-19, between January 2019 and January 2021. The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 33 publications
9
88
0
3
Order By: Relevance
“…Though not unexpected, the rise of PNs, many of which caused by CRA, brings a new challenge when it comes to HAI management. Increased rates of HAIs in ICUs that treat COVID-19 patients are being reported in various countries and support our findings [4,34], likely as a result of the inability to fully comply with the standard practices of infection control during this unprecedented time [12,35,36]. Another risk for promoting resistance in patients hospitalized for COVID-19 is the use of immunosuppressive therapy, though studies are showing conflicting results regarding its contribution to resistance [37,38].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Though not unexpected, the rise of PNs, many of which caused by CRA, brings a new challenge when it comes to HAI management. Increased rates of HAIs in ICUs that treat COVID-19 patients are being reported in various countries and support our findings [4,34], likely as a result of the inability to fully comply with the standard practices of infection control during this unprecedented time [12,35,36]. Another risk for promoting resistance in patients hospitalized for COVID-19 is the use of immunosuppressive therapy, though studies are showing conflicting results regarding its contribution to resistance [37,38].…”
Section: Discussionsupporting
confidence: 76%
“…Second, it also limited our ability to look at the interaction between antimicrobial use that extends beyond window of 48h before and after admission, given the established relationship of prolonged antimicrobial use and development of resistance [65]. And third, the extent to which immunosuppressive drugs (such as corticosteroids and/or tocilizumab) used in COVID-19 treatment played a role in the development of AMR [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with CRE, another important nosocomial threat is represented by CRAB secondary infections. To date, multiple outbreaks of CRAB have been reported in COVID-19-dedicated hospitals [43,[53][54][55][56][57]; in addition, a recent report from Italy demonstrated that the overall incidence of CRAB infections increased from 5.1 per 10,000 ICU-patientdays in January-April 2019 to 26.4 per 10,000 ICU-patient-days in January-April 2020, suggesting a worsening of CRAB spreading in ICUs strictly correlated with the occurrence of the COVID-19 pandemic [58]. Notably, CRAB infections and colonization represent an important risk factor for morbidity and mortality due to the extensive antimicrobial resistance spectrum of these bacteria and are a renowned complication of prolonged ICU stays.…”
Section: Carbapenem-resistant Non-fermenting Gram-negative Bacteriamentioning
confidence: 99%
“…For instance, MRSA, as a multidrug-resistant bacteria and common nosocomial infection pathogen, was isolated in the current study, and its growth was downregulated successfully through O3 gas application. MRSA is widely known to be highly prevalent in emergency departments and healthcare facilities [31,32]. Similarly, the diversity of Gram-positive bacteria was isolated in the current study, including Grampositive bacilli, CONS, bacillus, aerobic spore-forming, actinomycetes, diphtheroids spp., Nocardia, and Filamentous bacteria.…”
Section: O3 Gas Differently Controlled Bacterial Nosocomial Growth On Treated Medical Device Surfacesmentioning
confidence: 54%